Comparative politics - Caramani, Daniele (Oxford Univ. Press, 2011)
"Comparative Politics" provides a comprehensive introduction to political systems around the world. It covers methods and theories; the nation-state; institutions; actors and processes; policies; and recent changes
Literaturverz. S. [563] - 605
Mit Reg
Keywords: Einführung; Vergleichende politische Wissenschaft